2020
DOI: 10.5194/se-2020-48
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On morphology and amplitude of 2D and 3D thermal anomalies induced by buoyancy-driven flow within and around fault zones

Abstract: Abstract. In the first kilometres of the subsurface, temperature anomalies due to heat conduction processes rarely exceed 20–30 °C. When fault zones are sufficiently permeable, fluid flow may lead to thermal anomalies much higher, as evidenced by the emergence of thermal springs or by fault-related geothermal reservoirs. Hydrothermal convection triggered by buoyancy effects creates thermal anomalies whose morphology and amplitude are not well known, especially when depth- and time-dependent permeability are co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 71 publications
(118 reference statements)
0
6
0
Order By: Relevance
“…This will produce a temperature anomaly within the Pontgibaud hydrothermal system, but lateral thermal diffusion is observed within the fault zone itself, thus defining a larger geothermal reservoir. Indeed, considering a simplified 3D geometry, this lateral temperature diffusion has been highlighted in recent numerical models of fluid flow around faulted zones [33].…”
Section: Effect Of Stress Direction and Stress Intensity On The Fluidmentioning
confidence: 86%
See 2 more Smart Citations
“…This will produce a temperature anomaly within the Pontgibaud hydrothermal system, but lateral thermal diffusion is observed within the fault zone itself, thus defining a larger geothermal reservoir. Indeed, considering a simplified 3D geometry, this lateral temperature diffusion has been highlighted in recent numerical models of fluid flow around faulted zones [33].…”
Section: Effect Of Stress Direction and Stress Intensity On The Fluidmentioning
confidence: 86%
“…López and Smith [31] showed that temperature anomalies can be directly influenced by the permeability ratio between the fault and the host. 3D modeling based on TH coupling has shown the influence of this permeability ratio on the morphology of the temperature anomalies [33]. Our parametric study (Figures 11 and 12) made it possible to approach three factors influencing fluid flow: stress intensity, stress direction, and the permeability ratio between the fault and the basement.…”
Section: Effect Of Stress Direction and Stress Intensity On The Fluidmentioning
confidence: 98%
See 1 more Smart Citation
“…These focused on the thermal state of the basins (Bonté et al., 2018; Duddy et al., 1994) or on hydromechanical processes taking place at depth (Hairuo Qing & Mountjoy, 1992; Montegrossi et al., 2018). However, only a few studies investigated 3D Darcy flow coupled with thermal processes (Guillou‐Frottier et al., 2020; Przybycin et al., 2017; ). Compared to conductive static models of the GGB (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In the orogenic belt type, no abnormal heat source such as volcanic activity is required. Instead, local geothermal gradients and heat flows, themselves influenced by the radiogenic heat production, the rock rheology, the tectonic regime, and the topography, constitute the heat source and flow path of hot fluids (Guillou-Frottier et al, 2024). The combination of free-convection along permeable faults (Belgrano et al, 2016;Guillou-Frottier et al, 2020) and forced-convection induced by topographic gradients (Volpi et al, 2017;Sutherland et al, 2017;Wanner et al, 2019) ensures fluid circulation between the surface and the great depths in the forearc (Forster & Smith, 1989;López & Smith, 1995).…”
Section: Introductionmentioning
confidence: 99%